The urgence of developing strategic petrolium reserve (SPR) for Indonesia in facing military or non-millitarian threats - Setiawan Wijayanto; I Wayan Midhio; Muhammad Hadianto Wirajuda (Strategi Perang Semesta, 2022)
A country has strong energy security if it meets numerous criteria, including the availability of energy at reasonable rates, simple access to energy, and being totally accepted by the community while remaining environmentally conscious. Building a Strategic Petroleum Reserve (SPR) or a Petroleum Buffer Reserve is one strategy to attain national energy security (CPM). Many countries already have SPRs and are members of the International Energy Agency as a means of ensuring state uniformity in achieving national energy security and defending against the prospect of a global energy crisis. Several factors must be considered when developing the SPR to ensure that it is correctly developed in accordance with its objectives and benefits.